An ethical model for smart home-based elder care - Cao, Lina (Nursing ethics, 2025)
BackgroundThe smart home-based elder care presents a promising technological solution to address the challenges of aging. However, it has also unveiled a spectrum of ethical concerns, which may cause older adults to submit to negative emotions and psychological pressure.AimTo delineate the ethical dilemmas encountered by older adults in the context of smart home-based elder care, and to construct a model that elucidates the ethical issues across different dimensions.Research designThis study follows a qualitative phenomenological research design.Participants and research contextThe sample comprised 15 older adults and 10 adult children in two communities in Jinan, Shandong, China. Structured, in-depth interviews were performed to collect data and the Colaizzi descriptive analysis framework was adopted to analyze data. An ethical dilemma model was constructed based on framework of the Society Ecosystems Theory.Ethical considerationsThe proposal was approved by the Research Ethics Committee of the Second Hospital of Shandong University, China. Participation in this study was voluntary. Written and verbal consent was gained. All recordings were kept under the principle of confidentiality.ResultsEthical dilemmas of smart home-based elder care were grouped into three themes with 10 sub-themes, and a model composed of three systems was built based on these findings.DiscussionThe ethical dilemmas experienced by the older adults with smart home-based elder care were various and multi-layered, which could be elucidated by the ethical dilemma model.ConclusionThe model emphasizes the necessity for collaborative efforts among the whole society and the elderly individuals. Tailored support strategies should be implemented to address the ethical dilemmas of the macro, meso, and micro system. The results may improve the elderly population to receive a more content and convenient elder care experience.